Traditional sports games in Vojvodina in the function of diversification of tourism product - Bjeljac Željko; Ćurčić Nevena; Brankov Jovana; Milanović-Pešić Ana (Turističko Poslovanje, 2019)
Traditional sports games are an expression of folk creativity in the field of sports and recreation, the result of the creativity of the people in the culture of sport. According to the venue, they are mostly related to the rural areas from which they originated. Traditional sports games were recognized in the 21st century as an element of intangible cultural heritage, which should be protected and affirmed in a new way in order to preserve them from oblivion and disappearance. Therefore, the importance of traditional sports as an element of tourist off er (an important element of tourist off er and promotion of rural, religious, cultural, sports and recreational tourism) is increasingly recognized in tourism strategies and plans in the world. The subject of this research is 16 events that promote traditional sports games and skills in the territory of Vojvodina. The aim of the paper is to distinguish old traditional sports through tourism valorisation, which can represent an important segment in the diversification of tourism products. The methods used are analytical-synthetic and inductive-deductive methods with the use of critical inference, as well as methods of tourism valorization according to Hilary du Cros.